Development and application of chiral separation technology based on chiral metal-organic frameworks - Gege Zhu; Li Ge; Xinyu Li; Bing Niu; Qin Chen; Dan Zhong; Xiaodong Sun (Journal of Pharmaceutical Analysis)
Chirality is not only a natural phenomenon but also a bridge between chemistry and life sciences. An effective way to obtain a single enantiomer is through racemates resolution. Recent literature shows that chiral metal-organic frameworks (CMOFs) have many applications in various fields because of their diverse topologies and functionalities. This review outlines the design idea and summarizes the latest synthesis strategies and applications of CMOFs. It highlights key advances and issues in the separation domain. In conclusion, the review provides perspectives on the challenges and prospective advancements of CMOFs materials and CMOFs-based separation technologies.